KERUKUNAN ANTARUMAT BERAGAMA : STUDI IKATAN KEWARGAAN DAN ASOSIASIONAL PADA MASYARAKAT DESA PABUARAN KECAMATAN GUNUNG SINDUR BOGOR - ismail ismail (Balai Penelitian dan Pengembangan Agama Jakarta, 2021)
This paper examines inter-religious harmony in the community of Pabuaran Village, Gunung Sindur District, Bogor Regency which has been closely intertwined since time immemorial. This village is known as a harmonious village because the people can live side by side and harmoniously even though they consist of various ethnicities and religions. The harmony between religious believers in Pabuaran Village takes place naturally without any engineering. Even the houses of worship of five religions can stand without any rejection from the people of Pabuaran Village themselves and from the people around Pabauaran Village. Since this village was founded, there has never been an inter-religious conflict or been affected by the communal conflicts that occurred in various other areas in the archipelago. This research method uses a qualitative method with a case study approach. The data collection technique is done by means of observation, interviews and documentation studies. The main finding in this study is that the close interreligious harmony in Pabuaran Village is caused by several factors, including the existence of civic ties. The strong ties of citizenship are caused, among other things, by